A Legal Review of Share Inheritance in Limited Liability Companies - Achmad, Andyna Susiawati; Indradewi, Astrid Athina (Jurnal Ius Constituendum, 2025)
Conflicts over inherited company shares underscore ongoing legal uncertainties and highlight the need for a thorough legal review. The inheritance of shares in a Limited Liability Company (PT) is classified as a transfer of rights by operation of law (rechtsverkrijging onder algemene titel) as stipulated in the Indonesian Civil Code (KUHPerdata) and Law Number 40 of 2007 concerning Limited Liability Companies (Company Law). In principle, company shares are inheritable assets, and heirs have the right to receive them in accordance with inheritance laws. However, in practice, legal issues frequently arise when other shareholders object to heirs entering as new shareholders. This matter becomes more intricate when the company’s Articles of Association include clauses that limit the transfer of shares to external parties without the approval of current shareholders. This study aims to investigate the legal framework and practical application of share inheritance in limited liability companies in Indonesia. It employs a normative legal research method with statutory and conceptual approaches, drawing on secondary legal materials. The findings demonstrate that the inheritance of shares necessitates balancing the civil rights of heirs with the company’s interest in preserving business stability and continuity. This study presents a legal harmonization framework that has not been extensively explored in prior research. The innovation lies in its suggestion to harmonize inheritance law and corporate law to address potential conflicts and improve legal protection for both heirs and corporate stakeholders.